Ambiete de tanque-rede aumenta as interações agressivas e o estresse social na tilápia-do-Nilo - Boscolo, Camila Nomura Pereira [UNESP] (2014)
The social position (dominance or submission) in Nile tilapia is signalize through visual sound, and chemical information. Such signals can be reduced in cages, where the high rate of water renewal may dilute the chemical information environment. In addition, the cages do not have removable substrate, which also acts as a reducing of aggressive interactions for Nile tilapia. Thus, we tested the hypothesis that the concomitant absence of signals of social position in cages environment increases aggressive interactions and consequently the social stress in territorial fish. Groups of three male Nile tilapia (GIFT) were maintained in aquaria containing networks (imitating cages) and were tested in five treatments: 1. Substrate presence / without water renewal (Control 1). 2. Substrate presence / without water renewal - no network (Control 2). 3. Substrate presence/ plus water renewal. 4. Substrate absence / plus water renewal. 5. Substrate absence / without water renewal. The animals were grouped by two days, during which it was recorded (15 min / day) the frequency of aggressive interactions. We assess the social stability by means of reversals in social position (rank) of individuals and levels of Testosterone (T) and 11 - cetotestosterona (KT). We use cortisol and liver glycogen as an indicator of stress. The frequency of aggressive interactions and cortisol levels were higher in the treatments without removable substrate. Moreover, we observed that there was a higher rank reversal of the treatments with water renewal. Testosterone levels were higher in the treatments without removable substrate. KT was higher in treatments without damage to social cues. Thus, we conclude that the absence of indicators of social position arising from the cages environment increases aggressive interactions and social stress in Nile tilapia. Furthermore, we observed that the indicators of social position ...